Clinical Prole of Chronic Heart Failure in Hospitalized Type 2 Diabetic Patients (Ibrahim Cardiac Medical Journal, 2018)
Objective: To see the clinical profile of chronic heart failure in hospitalized type 2 diabetic subjects.Method: This cross-sectional study was carried out on a total of 100 type 2 diabetic patients with chronic heart failure, in the Department of Cardiology, BIRDEM, over a period of six months between July to December 2012.Results: The mean age of the study subjects was 60.9 ± 11.7 years with male to female ratio being roughly 2:1. The mean duration of diabetes mellitus was 9.15 years. Among the study subjects 72% were on insulin and 18% on oral hypoglycemic agents; 10% were on combined insulin and oral hypoglycemic agent. Dyspnea and cough were invariably present. About 88% subjects had edema, 39% raised JVP, and 13% murmur. Bilateral basal crepitation was found in 56% cases. While mean fasting blood glucose (FBG), postprandial blood glucose (PPBG) level and HbA1C were 10 mmol/l, 16.7 mmol/l and 9.9% respectively, mean serum creatinine was 2.07 mg/dl. Among study subjects, raised ESR (48%), elevated WBC count (50%) and raised BNP level (64.6%) were seen. Chest X- ray revealed cardiomagaly (70%), reticulonodular shadow in both lung fields (11%) and septal thickening (15%). ECG findings of the patients were old infarct (72%), IHD (66%), RV hypertrophy (40%) and arrhythmia (17%). Most common echocardiographic findings of the subjects were regional wall motion abnormalities (78%), Mild LV systolic dysfunction (64%) with Grade-I diastolic dysfunction being 70% and moderate to severe pulmonary arterial hypertension being 40%.Conclusion: Raised BNP level, presence of old infarct in ECG and regional wall motion abnormalities in echocardiography are the common clinical findings among patients with chronic heart failure.Ibrahim Card Med J 2016; 6 (1&2): 67-70